FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN MASYARAKAT NELAYAN PANTAI DI KABUPATEN BANTUL TAHUN 2012 - Daniel Halim; Y Sri Susilo (Modus, 2013)
This research aims to study aimed to determine the efect of venture capital variables, length of time at sea per trip and long business-to-income entrepreneurs in Bantul district fsheries. This research includes studies convienince sampling method, which is a procedure to get a sample unit according to the researcher desire. A total of 50 respondents were taken from four locations consisting of fshermen beach in Bantul, Yogyakarta.  From these results, the magnitude of the R-square of 0.915640, meaning the independent variables in this study were able to explain 91.56% of the dependent variable. Furthermore, from the results of t-test statistics explained that the venture capital variables, length of time at sea per trip and long business has signifcant positive efect on the income level of coastal fshing communities in Bantul. Keywords :  venture capital, length of time at sea per trip, old business, revenue